Crenotherapy: A neglected resource for human health now re-emerging on sound scientific concepts - Vaccarezza, Mauro; Vitale, M. (Springer, 2010)
Recent mechanistic evidence demonstrates that spa-based therapy (or, as we propose, crenotherapy from the Greek word ??e??, spring fountain) is indeed based on solid scientific data. This mini-review highlights the latest insights into the mechanisms of crenotherapy derived from in vitro experiments, studies on animal models, and carefully designed clinical trials. Although more basic and clinical data are still needed, crenotherapy is coming of age as a modern, scientifically sound therapy. As the underlying mechanisms are uncovered, it is becoming possible to choose the most appropriate applications of this centuries-old practice, possibly reducing medical costs, thus explaining the current worldwide renewed interest in crenotherapy. © 2010 ISB.